Growth development and natural infection incidence of tobacco mosaic virus (TMV) on silicon-treated chilli (Capsicum annuum L.) cultivated in commercial soil - Suhaizan Lob,; Mohammad Nurazri Mohd Aris,; Siti Nordahliawate Mohamed Sidique,; Nurul Faziha Ibrahim,; Jin, Xiaolei (Penerbit Universiti Kebangsaan Malaysia, 2017)
Chilli (Capsicum annuum L.) is one of the most important cultivated crops in Malaysia. It is largely cultivated for its fruits. The application of the chemical fertilizer solely is able to supply the desire nutrient for chilli plant but did not helping in resistant of pathogen attack. Therefore, this study attempts to determine the potential of silicon application on plant growth and disease resistant on treated plants. Chilli seedling were transplanted into individual polybag containing commercial soil and supplied with silicon at 0.5ml/L and 1.5ml/L concentrations for the period of 11 weeks. Control plants were supplied with water instead of silicon nutrient. Assessment was conducted from week 3 to 11 after transplanting. Result showed that the plant growth of chilli treated with both Si nutrient concentrations measured by plant height, leaf number, leaf diameter and stem diameter were significantly better than control plants. Besides, the natural occurrence of Tobacco Mosaic Virus (TMV) disease incidence observed on treated chilli were 26.7–44.4% reduced compared to control plants. This study provides the knowledge on the benefit of Silicon application on the cultivated chilli and could possibly help the farmers to produce higher and better quality of yield in the future.